Effects of different nitrogen sources on yield, chemical composition and nutritive value of Dal grass (Hymenachne amplexicaulis) (Bangladesh Veterinarian, 2010)
The effects of different sources of nitrogen on yield, chemical composition and nutritive value of Dal grass (Hymenachne amplexicaulis) were measured. Control (T0) had no fertilizer; T1 was treated with urea - 240 kg N/ha; T2 with cow manure-25.8 tonnes (t)/ha; T3 with goat manure-13.2 t/ha; T4 with rabbit manure-7.6 t/ha and T5 with poultry manure-5.9 t/ha. All treatments provided the same amount of nitrogen. Experiment was conducted following completely randomized design (CRD) with four replications in each treatment. In the first cutting maximum green forage (33.3 & 31.1), dry matter (7.7 & 7.1) and organic matter (7.1 & 6.5) MT/ha were obtained (p0.05) difference in organic matter digestibility and metabolizable energy content of Dal grass between treatments. It is suggested that poultry manure may be recommended as a source of nitrogen fertilizer for Dal grass production in Bangladesh. DOI: 10.3329/bvet.v25i2.4621 Bangl. vet. 2008. Vol. 25, No. 2, 75-81